Calvatia pyriformis : A New Record in Indonesia - Rudy Hermawan; Ivan Permana Putra (Justek : Jurnal Sains dan Teknologi, 2018)
Abstract: Calvatia has the unique form as puffball mushroom. Currently, it is classified in Basidiomycota and Lycoperdaceae. This research aimed to characterize the Calvatia species based on morphological data. Fruiting body of Calvatia was found on the grass with single colony as saprobic mushroom. Fruiting body of Calvatia was collected, observed, and preserved using Formalin Acetic Alcohol (FAA).T he spores are produced internally in a gasterothecium. It is looked like pear-shaped or puffball-shaped, yellow to brownish outside and inside, the granular outer surface, thin layer of exoperidium, and soft texture of fruiting body. Basidiospore is finely globose to ovoid and free of ornament. The capillitium was swollen and septate. The specimen is identified as Calvatia pyriformis.Abstrak:Calvatia memiliki bentuk unik sebagai jamurbola. Saatini, Calvatia di klasifikasikan ke dalam Basidiomycota dan Lycoperdaceae. Studi ini bertujuan untuk mengkarakterisasi spesies Calvatia berdasarkan data morfologi. Tubuh buah Calvatia tumbuh di rumput secara soliter sebagai jamur sparob. Tubuh buah jamur dikoleksi, diobservasi, dan dipreservasi dengan menggunakan Formalin Acetic Alcohol (FAA). Spora-spora diproduksi secara internal di dalam sebuah gasterothecium. Spesimen ini berbentuk seperti pir atau bola permukaan dan bagian dalamnya berwarna kuning kecoklatan, terdapat alur granular pada permukaannya, lapisan exoperidium tipis, dan teksturnya lembut. Basidiospora berbentuk globose sampai seperti ovoid dan tidak ada ornamentasi. Hifa kapillituim berbentuk membengkak dan ada sekat. Spesimen ini diidentifikasi sebagai Calvatia pyriformis.